Fibrillization of Non‐Fullerene Acceptors Enables 19% Efficiency Pseudo‐Bulk Heterojunction Organic Solar Cells. Issue 6 (18th December 2022) - Li, Donghui; Deng, Nan; Fu, Yiwei; Guo, Chuanhang; Zhou, Bojun; Wang, Liang; Zhou, Jing; Liu, Dan; Li, Wei; Wang, Kai; Sun, Yanming; Wang, Tao
Abstract: The structural order and aggregation of non‐fullerene acceptors (NFA) are critical toward light absorption, phase separation, and charge transport properties of their photovoltaic blends with electron donors, and determine the power conversion efficiency (PCE) of the corresponding organic solar cells (OSCs). In this work, the fibrillization of small molecular NFA L8‐BO with the assistance of fused‐ring solvent additive 1‐fluoronaphthalene (FN) to substantially improve device PCE is demonstrated. Molecular dynamics simulations show that FN attaches to the backbone of L8‐BO as the molecular bridge to enhance the intermolecular packing, inducing 1D self‐assembly of L8‐BO into fine fibrils with a compact polycrystal structure. The L8‐BO fibrils are incorporated into a pseudo‐bulk heterojunction (P‐BHJ) active layer with D18 as a donor, and show enhanced light absorption, charge transport, and collection properties, leading to enhanced PCE from 16.0% to an unprecedented 19.0% in the D18/L8‐BO binary P‐BHJ OSC, featuring a high fill factor of 80%. This work demonstrates a strategy for fibrillating NFAs toward the enhanced performance of OSCs. Abstract : Fibrillization of non‐fullerene acceptor L8‐BO is realized by employing a conjugated fused‐ring solvent additive 1‐fluoronaphtalene that acts as the molecular bridge, which contributes to realize a power conversion efficiency of 19% in the pseudo‐bulk heterojunction D18/L8‐BO binary organic solar cell, featuring a high fill factor of 80% with improved charge transport.